The Application of Industrial 4.0 Assets Maintenance Strategy to Improve Productivity Level at Energy Industry Customers - Muhammad Fikri; Widhyawan Prawiraatmadja (Journal of International Conference Proceedings (JICP), 2019)
The productivity level at hydrocarbon processing and energy companies can be affected by unplanned shutdown of assets which leads to significant business loss such as lost production, wasted labor, depleted inventory, and higher exposure to safety risks. As an energy company, unplanned shutdowns could cause another multiplier negative effect aside from financial and operations. It would take days or weeks for the markets to adjust to the sudden loss of the production, resulting the price impact and scarcity of hydrocarbon products in the market would impact the nation’s economy and potentially create a political disturbance. This journal scope would discuss on the unplanned shutdown as the main business issue and how the proposed Industry 4.0 technology solutions on preventing the causes and explanations to transform the current company operations to improve the productivity. The proposed solutions can be acquired by an energy company as a reference to enhance its existing assets maintenance strategy to be a part of improvement process. There are three companies which are included as part of the journal assessment; Company A (Fluid Catalytic Cracking), Company B (Geothermal Power Utility), and Company C (Liquified Natural Gas Plant).